PENGARUH EFEKTIVITAS SISTEM INFORMASI AKUNTANSI, KEMAMPUANTEKNIK PEMAKAI, DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KINERJA INDIVIDU PADA LEMBAGA PERKREDITAN DESA (LPD) PEMAKAI SISTEM LPD DIGITAL DI KOTA MADYA DENPASAR - Gusti Ayu Sri Puspa Dewi; I Wayan Sudiana (Hita Akuntansi dan Keuangan, 2020)
Individual performance is the ability of individuals to do things successfully and efficiently in a company. Competitive advantage can be achieved through service quality, work quality, timeliness, supervisory supervision, cost effectiveness, and the influence of colleagues from each individual. This study aims to obtain empirical evidence regarding the Effectiveness of AIS, User's Technical Capabilities, and Utilization of Information Technology on Individual Performance. The method of determining the sample in this study was carried out by using purposive sampling technique. The population of this study were all Village Credit Institutions employees in 11 Village Credit Institutions in Denpasar who had used a digital system totaling 237 people with a sample of 53 people. The data analysis technique used is Multiple Linear Regression Analysis using SPSS programs. Based on the results of data analysis shows that the effectiveness of the AIS affects the performance of the individual, while the Technical Capability of the User and the Utilization of Information Technology has no effect on the individual's performance.